2001
DOI: 10.2170/jjphysiol.51.281
|View full text |Cite
|
Sign up to set email alerts
|

Brain Angiotensin and Body Fluid Homeostasis.

Abstract: The circulating hormone angiotensin II is an important humoral factor regulating cardiovascular and body fluid and electrolyte homeostasis. Potent direct constrictor actions on the vasculature, stimulation of the sodium-retaining hormone aldosterone from the adrenal cortex, generation of thirst and sodium appetite, release of the urine-concentrating hormone vasopressin, intrarenal regulation of tubular-glomular balance, and feedback inhibition of renal renin release are just some of the well recognized actions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
45
0
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 75 publications
2
45
0
3
Order By: Relevance
“…Early studies demonstrated the role of this GPCR subfamily in fluid homeostasis. Treatment with angiotensin II in mice inhibits drinking of water or saline, whereas administration of angiotensin II receptor antagonists stimulates diverse responses including water drinking, vasopressin secretion, and natriuresis (31,32). In addition, experiments on dogs showed that bradykinin regulates proximal tubular sodium reabsorption (33).…”
Section: Discussionmentioning
confidence: 99%
“…Early studies demonstrated the role of this GPCR subfamily in fluid homeostasis. Treatment with angiotensin II in mice inhibits drinking of water or saline, whereas administration of angiotensin II receptor antagonists stimulates diverse responses including water drinking, vasopressin secretion, and natriuresis (31,32). In addition, experiments on dogs showed that bradykinin regulates proximal tubular sodium reabsorption (33).…”
Section: Discussionmentioning
confidence: 99%
“…ANG II produces an increase in arterial pressure due to both a direct vasoconstrictor effect, mediated by AT 1 receptors in blood vessels, and a central sympathoexcitatory effect. Peripheral ANG II binds to receptors in the circumventricular organs of the brain, including the organum vasculosum of the lamina terminalis and the subfornical organ (29). These sites, in turn, send projections to several other nuclei that activate the sympathetic nervous system, increasing arterial pressure and regulating fluid balance.…”
mentioning
confidence: 99%
“…There also is evidence of a central renin-angiotensin system (RAS) that contributes to stress responses (6,23,41). Endogenous ANG II can be found in numerous periventricular locations (29), and ANG II receptors (both AT 1 and AT 2 ) are located within the hypothalamus, brain stem, and pituitary (45). The central RAS also has been implicated in long-term regulation of arterial pressure and the etiology of hypertension (3,35,36,42).…”
mentioning
confidence: 99%
“…It is generally accepted that the central angiotensin II-induced cardiovascular and endocrine responses such as induction of drinking and dipsogenic effects, pressor response and release of AVP are mediated by AT 1 receptors [25,18]. Furthermore, central injection of AT 1 receptor antagonist, Losartan, blocks AT 1 receptors and influences on central angiotensin mechanisms [24,26]. Infusion of Ang II into a lateral cerebral ventricle produce an increase in blood pressure [27,20,28], increase in mean arterial pressure [29,30], decrease in urine flow [27], regulate hydromineral balance [22], induce the pressor response [31], stimulate AVP and OT release [20,28] and elevate RSNA (renal sympathetic nerve activity) [32].…”
Section: Discussionmentioning
confidence: 99%